Complete response of a colonic high-grade neuroendocrine carcinoma to platinum-based therapy: Insights from comprehensive genomic profiling. (28th October 2021) - Wood, R; Arnason, T; DeCoste, R; Gaston, D; Carter, M D; Rayson, D
Abstract: Introduction/Objective: Comprehensive genomic profiling (CGP) is an essential tool in precision medicine, providing diagnostic, prognostic, and predictive (therapeutic) information to enable personalized and optimized care for cancer patients. We present the case of a patient with a metastatic high-grade tumor of the colon who showed an impressive response to systemic therapy and discuss the role of CGP in cancer management. Methods/Case Report: A 54-year-old woman with was diagnosed with stage IV large-cell neuroendocrine carcinoma (LCNEC) of the colon with large volume liver and nodal metastases with imminent hepatic failure. CGP was performed on the resected tumor (TSO500 panel, 523 cancer-related genes, Illumina), showing pathogenic mutations in multiple oncogenes and tumor suppressor genes, including BRCA1, BAP1, and BRAF. Additionally, global parameters revealed a very high tumor mutation burden (TMB, 351 / Mb), and high-degree microsatellite instability (MSI-H). Treatment of the patient's metastases with platinum-based systemic therapy resulted in a complete radiographic response, with no evidence of disease recurrence after 6.5 years. This type of complete response to therapy is rarely reported in colonic LCNEC. Assessment by Medical Genetics did not identify a germline mutation suggestive of hereditary breast/ovarian cancer or Lynch syndrome. Results (if a Case Study enter NA): NA Conclusion: The patient's extraordinary response to therapy is likely due to loss of BRCA1 and/or BAP1 function, as deleterious mutations in both genes predict sensitivity to platinum-based therapy through exploitation of deficient homologous recombination repair (HRR). The high TMB and MSI-H status suggest the immune system may have contributed to tumor clearance through neoantigen activation of T-cells. The information provided by CGP also suggested potential tumor sensitivity to poly(ADP-Ribose) polymerase inhibitors (PARPi), immunotherapy (IT), and BRAF/MEK inhibitor therapy, should the tumor recur. This case highlights the value of CGP in guiding management of rare and aggressive tumors.